Effect of 6-Month Calorie Restriction and Exercise on Serum and Liver Lipids and Markers of Liver Function - Larson-Meyer, D. Enette; Newcomer, Bradley R; Heilbronn, Leonie K; Volaufova, Julia; Smith, Steven R; Alfonso, Anthony J; Lefevre, Michael; Rood, Jennifer C; Williamson, Donald A; Ravussin, Eric (Obesity (Silver Spring, Md.), 2008)
Objective: Nonalcoholic fatty liver disease (NAFLD) and its association with insulin resistance are increasingly recognized as major health burdens. The main objectives of this study were to assess the relation between liver lipid content and serum lipids, markers of liver function and inflammation in healthy overweight subjects, and to determine whether caloric restriction (CR) (which improves insulin resistance) reduces liver lipids in association with these same measures. Methods and Procedures: Forty‐six white and black overweight men and women (BMI = 24.7–31.3 kg/m2) were randomized to “control (CO)” = 100% energy requirements; “CR” = 25%; “caloric restriction and increased structured exercise (CR+EX)”= 12.5% CR + 12.5% increase in energy expenditure through exercise; or “low‐calorie diet (LCD)” = 15% weight loss by liquid diet followed by weight‐maintenance, for 6 months. Liver lipid content was assessed by magnetic resonance spectroscopy (MRS) and computed tomography (CT). Lipid concentrations, markers of liver function (alanine aminotransferase (ALT), alkaline phosphatase (ALK)), and whole‐body inflammation (tumor necrosis factor‐α (TNF‐α), interleukin‐6 (IL‐6), high‐sensitivity C‐reactive protein (hsCRP)) were measured in fasting blood. Results: At baseline, increased liver lipid content (by MRS) correlated (P < 0.05) with elevated fasting triglyceride (r = 0.52), ALT (r = 0.42), and hsCRP (r = 0.33) concentrations after adjusting for sex, race, and alcohol consumption. With CR, liver lipid content was significantly lowered by CR, CR+EX, and LCD (detected by MRS only). The reduction in liver lipid content, however, was not significantly correlated with the reduction in triglycerides (r = 0.26; P = 0.11) or with the changes in ALT, high‐density lipoprotein (HDL)‐cholesterol, or markers of whole‐body inflammation. Discussion: CR may be beneficial for reducing liver lipid and lowering triglycerides in overweight subjects without known NAFLD.